2004
DOI: 10.1029/2003jd004105
|View full text |Cite
|
Sign up to set email alerts
|

Molecular composition of the water‐soluble fraction of atmospheric carbonaceous aerosols collected during ACE‐Asia

Abstract: [1] During the Asian Pacific Regional Aerosol Characterization Experiment (ACE-Asia), samples of carbonaceous aerosols were collected on board the Center for Interdisciplinary Remotely Piloted Aircraft Studies (CIRPAS) De Havilland DHC-6 Twin Otter aircraft. The samples were analyzed to determine their total carbon (TC) and water-soluble organic compound (WSOC) contents as well as to identify the individual compounds comprising the WSOC fraction of the aerosol. The TC concentrations varied from 3.5 to 14.3 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 51 publications
5
71
1
Order By: Relevance
“…50% of the organics were found to be watersoluble (WSOC); other field studies have also reported WSOC concentrations of 30-70% of the total organics (Sempere and Kawamura 1994;Mader et al 2004).…”
Section: Estimation Of Molecular Weight Of Organic Components In Ambimentioning
confidence: 99%
“…50% of the organics were found to be watersoluble (WSOC); other field studies have also reported WSOC concentrations of 30-70% of the total organics (Sempere and Kawamura 1994;Mader et al 2004).…”
Section: Estimation Of Molecular Weight Of Organic Components In Ambimentioning
confidence: 99%
“…Several types of L-amino acids have been identified in marine atmospheric aerosol samples ( Fig. 1), including, proline (PRO), serine (SER), glycine (GLY), alanine (ALA), valine (VAL), methionine (MET) and phenylalanine (PHE) (Mace et al, 2003a, b, c;Zhang and Anastasio, 2003;Malder et al, 2004;Wedyan and Preston, 2008). Over the central Arctic Ocean reaction products of L-methionine was suggested as being responsible for observed periods of new particle formation (Leck and Bigg, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of secondary The DFAAs are shown in decreasing order of abundance (Malder et al, 2004): THR: threonine, GLU: glutamic acid, ASP: asparagine, CYS: cysteine, LYS: lysine, TYR: tyrosine, LEU: leucine, ILE: iso-leucine, HIS: histidine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic matter can be 20-50 % of the total fine aerosol mass (Saxena and Hildemann, 1996;Putaud et al, 2004), and as high as 90 % over biomass burning regions during burning season (Andreae and Crutzen, 1997;Talbot et al, 1988Talbot et al, , 1990Artaxo et al, 1988Artaxo et al, , 1990Roberts et al, 2001;Bond et al, 2004). Between 45 and 75 % of this organic matter is watersoluble organic carbon (WSOC) and may therefore influence the hygroscopic growth behavior of atmospheric aerosols (Decesari et al, 2005;Saxena and Hildemann, 1996;Mader et al, 2004). This influence has been the subject of ongoing research during the past decade, though our knowledge is still limited (Kanakidou et al, 2005;Zhang et al, 2007;Hallquist et al, 2009).…”
mentioning
confidence: 99%